Pragmatics and its Role on Developing Linguistic Studies - Al-Youbi, Maha Najm Saleem (Arts for Linguistic & Literary Studies, 2025)
This study aims to explore the concepts of pragmatics, the reasons behind the diversity of its definitions, and its impact on linguistic studies. It also highlights the contributions of pragmatics pioneers to the advancement of linguistic studies by diversifying linguistic study tools and incorporating pragmatic procedures alongside existing structuralist and generative linguistic mechanisms. Pragmatics scholars have focused on analyzing language in actual usage across different contexts, considering speakers' intentions and the conditions of their interlocutors. The study is structured into an introduction and two main sections. The first section examines pragmatics, its concept, scientific background, development, and various evolutionary stages. The second section discusses the key figures in pragmatics and their conceptual contributions. The study concludes that pragmatics is a modern linguistic discipline concerned with language use while maintaining a focus on meaning. Unlike traditional linguistic approaches, pragmatics did not emerge solely from linguistic studies; philosophy played a significant role in its inception and evolution. The diversity of pragmatics definitions stems from its intersection with multiple disciplines, including philosophy, psychology, and sociology.